Reliability and validity of psychosocial and environmental correlates measures of physical activity and screen-based behaviors among Chinese children in Hong Kong - Salmon Jo; Wong Stephen H; Huang Ya-Jun; Hui Stanley S (BMC, 2011)
Abstract Background Insufficient participation in physical activity and excessive screen time have been observed among Chinese children. The role of social and environmental factors in shaping physical activity and sedentary behaviors among Chinese children is under-investigated. The purpose of the present study was to assess the reliability and validity of a questionnaire to measure child- and parent-reported psychosocial and environmental correlates of physical activity and screen-based behaviors among Chinese children in Hong Kong. Methods A total of 303 schoolchildren aged 9-14 years and their parents volunteered to participate in this study and 160 of them completed the questionnaire twice within an interval of 10 days. Intraclass correlation coefficients (ICCs), kappa statistics, and percent agreement were performed to evaluate test-retest reliability of the continuous and categorical variables, respectively. Exploratory factor analyses (EFAs) were conducted to assess convergent validity of the emergent scales. Cronbach's alpha and ICCs were performed to assess internal and test-retest reliability of the emergent scales. Criterion validity was assessed by correlating psychosocial and environmental measures with self-reported physical activity and screen-based behaviors, measured by a validated questionnaire. Results Reliability statistics for both child- and parent-reported continuous variables showed acceptable consistency for all of the ICC values greater than 0.70. Kappa statistics showed fair to perfect test-retest reliability for the categorical items. Adequate internal consistency and test-retest reliability were observed in most of the emergent scales. Criterion validity assessed by correlating psychosocial and environmental measures with child-reported physical activity found associations with physical activity in the self-efficacy scale (r = 0.25, P < 0.05), the peer support for physical activity scale (r = 0.25, P < 0.05) and home physical activity environmental (r = 0.14, P < 0.05). Children's screen-based behaviors were associated with the family support for physical activity scale (r = -0.22, P < 0.05) and parental role modeling of TV (r = 0.12, P = 0.053). Conclusions The findings provide psychometric support for using this questionnaire for examining psychosocial and environmental correlates of physical activity and screen-based behaviors among Chinese children in Hong Kong. Further research is needed to develop more robust measures based on the current questionnaire, especially for peer influence on physical activity and parental rules on screen-based behaviors.